The threatened Dioscorea galiiflora and the identification of Dioscorea triangularis (Dioscoreaceae): Solving a secular imbroglio - Fraga, Fernanda Ribeiro De Mello; Couto, Ricardo Sousa; Braga, João Marcelo Alvarenga (Phytotaxa, 2019)
Based on reproductive characters, two taxa are segregated from D. triangularis (Griseb.) R. Knuth: D. piperifolia var. triangularis and D. galiiflora, the latter previously known only by its type collection. Dioscorea galiiflora is here described, new occurrences are reported and its conservation status is assessed. We also provide nomenclatural notes and circumscribe D. piperifolia var. triangularis, D. galiiflora and D. moyobambensis.